2015
DOI: 10.1016/j.gecco.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

High carbon stocks in roadside plantations under participatory management in Bangladesh

Abstract: a b s t r a c tPlantations are important REDD+strategies for increasing carbon sequestration while enhancing local livelihoods. Reforestation along roads and highways under participatory forest management in southwestern Bangladesh could contribute to REDD+. This study assessed the diversity and structure of roadside plantations in order to develop a basal area based generalized allometric model for estimating above-and below-ground tree biomass carbon in Southwestern Bangladesh. All woody plants with d.b.h. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 40 publications
5
44
3
Order By: Relevance
“…Followed by Azadirachta The high biomass of institutions in Nagpur (137 t ha −1 ) is comparable to Pune University campus (108 t ha −1 ) studied by Waran and Patwardhan, while in park and garden (150 t ha −1 ) have higher biomass as compared to gardens studied in Pune (110 t ha −1 ) [31]. For road, estimated biomass ranged from the value 56.75-380.11 t ha −1 recorded by Rahman et al in Bangladesh [63]. As for the estimate of biomass (236 t ha −1 ) in forest, the value is within the identified national range for tropical dry deciduous forest 83-370 t ha −1 and 33-315 t ha −1 as studied Joshi et al and Gandhi et al respectively [64,65].…”
Section: Characteristics Of Dominant Speciesmentioning
confidence: 69%
“…Followed by Azadirachta The high biomass of institutions in Nagpur (137 t ha −1 ) is comparable to Pune University campus (108 t ha −1 ) studied by Waran and Patwardhan, while in park and garden (150 t ha −1 ) have higher biomass as compared to gardens studied in Pune (110 t ha −1 ) [31]. For road, estimated biomass ranged from the value 56.75-380.11 t ha −1 recorded by Rahman et al in Bangladesh [63]. As for the estimate of biomass (236 t ha −1 ) in forest, the value is within the identified national range for tropical dry deciduous forest 83-370 t ha −1 and 33-315 t ha −1 as studied Joshi et al and Gandhi et al respectively [64,65].…”
Section: Characteristics Of Dominant Speciesmentioning
confidence: 69%
“…Findings of this study showed the highest IVI for Swietenia macrophylla(193.22) followed by Polyalthia longifolia (184.59) and Samanea saman (138.87) (Table 2). Similar study was conducted in the urban parks of Bangalore, India where IVI value found for Polyalthia longfolia 34.9 [64], 28.37 for Swietenia macrophylla in the metropolitan area of Chittagong [65], 77.1 for Swietenia macrophylla in the urban forest of Sri Lanka [66] and 21.41 for Samanea saman, and 2.01 for Swietenia macrophylla in the roadsides of Southwestern Bangladesh[30]. The high Importance Value Index (IVI) of these species in green areas of Dhaka south city indicates their dominance, good power of regeneration, their growth habits and potential to tolerate diverse environmental condition of urban settlement.…”
mentioning
confidence: 54%
“…In parks and gardens, 20 meter plot to plot distance was maintained whereas in play grounds 10 meter distance was adopted. In roadsides, plots were taken in a zigzag manner on both the sides of road ( Figure 2), in order to maintain variation and 100 meter plot to plot distance was maintained [30].…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…This estimation included a common wood density value (0.57 t•m −3 ) and a fixed biomass expansion factor (6) (FD, 2007) which may result in uncertainty in biomass estimation by considering a lower wood density and a higher fixed value of biomass expansion factor (Penman et al, 2003). During the year 2009, pan-tropical model of Chave et al (2005) was also used to estimate the biomass and carbon stock of the Sundarbans of Bangladesh (Rahman et al, 2015). The used pan-tropical model is capable to generalize poorly with its polynomial function that results in implausible relationship among biomass and diameter of trees (Sileshi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…pan-tropical biomass model of Brown et al (1989) and Chave et al (2005) were commonly used to estimate the biomass and carbon stock in plantation and natural forests of Bangladesh like Miah et al (2009), Ullah & Al-Amin (2012), Rahman et al (2015). Numerous studies demonstrated that pan-tropical models generate higher bias in biomass estimation compared to locally developed models (Vieira et al, 2008;Basuki et al, 2009;Kenzo et al, 2009;Ngomanda et al, 2014;Maulana et al, 2016).…”
Section: Introductionmentioning
confidence: 99%